2013
DOI: 10.1074/jbc.m112.442889
|View full text |Cite
|
Sign up to set email alerts
|

The Hyaluronan Receptor for Endocytosis (HARE) Activates NF-κB-mediated Gene Expression in Response to 40–400-kDa, but Not Smaller or Larger, Hyaluronans

Abstract: Background: HARE mediates systemic clearance of hyaluronan (HA), which turns over continuously in tissues. Results: HARE uptake of 40 -400-kDa, but not larger or smaller, HA stimulated NF-B activation. Conclusion: HA-HARE signal complexes activate NF-B and gene transcription only with optimally sized HA. Significance: HARE responsiveness to a narrow size range of HA degradation products may be a sensing system to detect tissue ECM stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
95
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(100 citation statements)
references
References 62 publications
1
95
0
4
Order By: Relevance
“…HA-induced p38 phosphorylation has been previously described as an effect of HA signaling through CD44 (97). HA-induced ERK1/2 phosphorylation has been also previously observed, mainly as an effect driven through RHAMM (98) and/or RHAMM and EGF receptor cooperation (99), via CD44 and EGF receptor interaction (100) or STAB2 (90). Here, we showed that after TLR4 but not CD44 knockdown, ERK1/2, p38, and JNK phosphorylation was decreased in response to HA treatment (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…HA-induced p38 phosphorylation has been previously described as an effect of HA signaling through CD44 (97). HA-induced ERK1/2 phosphorylation has been also previously observed, mainly as an effect driven through RHAMM (98) and/or RHAMM and EGF receptor cooperation (99), via CD44 and EGF receptor interaction (100) or STAB2 (90). Here, we showed that after TLR4 but not CD44 knockdown, ERK1/2, p38, and JNK phosphorylation was decreased in response to HA treatment (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…CS types A, C, D, and E and DS were from Seikagaku (Japan), and AcLDL was from Kalen Biomedicals (Montgomery Village, MD). Narrow size-range HA preparation of 14, 80, 107, and 178 kDa were made and characterized as described earlier (17). Commercial HA preparations of 51, 741, and 2600 kDa were obtained from Lifecore Biomedical, LLC (Chaska, MN), and 133-kDa Select-HA TM was from Hyalose, LLC (Oklahoma City, OK).…”
Section: Methodsmentioning
confidence: 99%
“…Commercial HA preparations of 51, 741, and 2600 kDa were obtained from Lifecore Biomedical, LLC (Chaska, MN), and 133-kDa Select-HA TM was from Hyalose, LLC (Oklahoma City, OK). All HA weight-average mass values were determined by size exclusion chromatography coupled to multiangle light scattering analysis (17,22,23). Enhanced Chemiluminescence substrate for Western blot analysis was from PerkinElmer Life Sciences.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HA fragments stimulate cell signaling cascades through specific cell surface receptors (Stern et al 2006), such as CD44 (Noble 2002;Ohno et al 2006), RHAMM (Zhang et al 1998;Turley et al 2002) and HARE/Stab2 (Kyosseva et al 2008). There is a very narrow-range HA size dependence for both ERK1/2 and NF-κB signaling during HARE-mediated HA endocytosis (Pandey et al 2013). Although all HA sizes are bound and endocytosed by HARE, only 40-400 kDa HA stimulates signaling; larger or smaller HA does not activate ERK1/2 or NF-κB.…”
Section: Introductionmentioning
confidence: 99%